International financial governance under stress : global structures versus national imperatives - Underhill, Geoffrey R. D.; Zhang, Xiaoke (Global economic institutions., 2003)
The Asian and Argentinian financial crises have focused attention on the most appropriate shape and role for international and national financial institutions. This volume offers a wide-ranging overview of the problems and possible policy responses. Although the approach is multi-disciplinary, most of the contributors write from a political economy perspective.